Ageing and multiple sclerosis - Isačenko, Julija; Balnytė, Renata (Neurologijos seminarai, 2024)
Advances in the treatment of multiple sclerosis in recent decades have allowed an increasing number of people to reach advanced age without significant disability. Most disease-modifying drugs are designed to suppress active inflammation and reduce the risk of relapses; however, as patients age, the pathogenetic mechanisms of the disease change, and progression independent of relapse activity (PIRA) begins to prevail. The prolonged duration of drug-induced immunosuppression, combined with age-related comorbidities, may lead to adverse effects. In this article, we review age-related changes in multiple sclerosis pathogenesis and the associated treatment challenges.
Keywords: multiple sclerosis; disease-modifying therapies; aging